Penerapan Algoritma Genetika Pada Optimasi Penjadwalan Matakuliah Pada Perguruan Tinggi STMIK Mulia Darma - Sihombing, Monang Juanda Tua; M.Rajagukguk, Denni; Panjaitan, Muhammad Iqbal; Manalu, Mamed Rofendi; Simangunsong, Pandi Barita Nauli; Sridewi, Nurmala (Universitas Budi Darma, 2024)
This research aims to produce an optimal course schedule at STMIK Mulia Darma, with the aim of reducing the number of conflicting courses, equalizing the student burden, and maximizing the use of classrooms. The optimization process is carried out through determining the course schedule using a genetic algorithm. Genetic algorithms were chosen because of their ability to solve large-scale and complex problems, making them suitable for handling complex course scheduling problems that involve many variables and constraints. It is hoped that the results of this study will produce an optimal course schedule, taking into account course clashes, student loads, and classroom use efficiency. After research, the optimal course schedule was obtained.